IMPACTO DA DUPLA-TAREFA COM SMARTPHONE SOBRE O EQUILÍBRIO DE ADULTOS JOVENS: INVESTIGAÇÃO EM AMBIENTE CONTROLADO E NÃO-CONTROLADO - SIDNEY AFONSO SOBRINHO JUNIOR (2022)
Using smartphones during a secondary motor task can be detrimental for the overall motor performance. The aim of this dissertation was to determine the risks of accidents caused by the use of smartphones by pedestrians while walking in a controlled (laboratory) and non-controlled (public street) environment. Two hundred and one participants were submitted to walking activities while texting messages and talking on the phone. Assessments were performed with no external distractors (laboratory) and on a public street, with vehicles, pedestrians, lights and noises. Multivariate analysis of variance tests provided main effect of task (using × not using cell phone), environment (laboratory × street), sex (male × female) and interactions. Significance was set at 5%. Results showed that using smartphone while walking increases risks of accidents of pedestrians (main effect of task: 0.84; p=0.001). The risk of accident was higher on the streets when compared to the laboratory assessment (main effect of environment: 0.82; p=0.001). There was no difference of risks between men and women (main effect of sex: 0.01; p=0.225), whether in the laboratory or on the street (main effect of sex × environment: 0.01; p=0.905). Task × environment interaction showed that real life traffic distractors potentiate risks of accidents of pedestrians (main effect of task × environment: 0.41; p=0.001). In conclusion, this dissertation found that using smartphone while walking can be risky for pedestrians, especially in a traffic environment. People should avoid using their smartphone while crossing streets. Keywords: Smartphone. Pedestrian. Multitasking Behavior. Traffic accidents.